Contrast-enhanced time-resolved 4D MRA of congenital heart and vessel anomalies: image quality and diagnostic value compared with 3D MRA. - Vogt, Florian M; Theysohn, Jens M; Michna, Dariusz; Hunold, Peter; Neudorf, Ulrich; Kinner, Sonja; Barkhausen, Jörg; Quick, Harald H (European Radiology, 2013)
Objectives: To evaluate time-resolved interleaved stochastic trajectories (TWIST) contrast-enhanced 4D magnetic resonance angiography (MRA) and compare it with 3D FLASH MRA in patients with congenital heart and vessel anomalies.Methods: Twenty-six patients with congenital heart and vessel anomalies underwent contrast-enhanced MRA with both 3D FLASH and 4D TWIST MRA. Images were subjectively evaluated regarding total image quality, artefacts, diagnostic value and added diagnostic value of 4D dynamic imaging. Quantitative comparison included signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR) and vessel sharpness measurements.Results: Three-dimensional FLASH MRA was judged to be significantly better in terms of image quality (4.0 ± 0.6 vs 3.4 ± 0.6, P < 0.05) and artefacts (3.8 ± 0.4 vs 3.3 ± 0.5, P < 0.05); no difference in diagnostic value was found (4.2 ± 0.4 vs 4.0 ± 0.4); important additional functional information was found in 21/26 patients. SNR and CNR were higher in the pulmonary trunk in 4D TWIST, but slightly higher in the systemic arteries in 3D FLASH. No difference in vessel sharpness delineation was found.Conclusions: Although image quality was inferior compared with 3D FLASH MRA, 4D TWIST MRA yields robust images and added diagnostic value through dynamic acquisition was found. Thus, 4D TWIST MRA is an attractive alternative to 3D FLASH MRA.Key Points: • New magnetic resonance angiography (MRA) techniques are increasingly introduced for congenital cardiovascular problems. • Time-resolved angiography with interleaved stochastic trajectories (TWIST) is an example. • Four-dimensional TWIST MRA provided inferior image quality compared to 3D FLASH MRA but without significant difference in vessel sharpness. • Four-dimensional TWIST MRA gave added diagnostic value.